‘Diaphaneitè’ Pater’s Enigmatic Term - Morito Uemura (Cahiers Victoriens et Edouardiens, 2008)
This paper asserts that Pater’s essay title, ‘Diaphaneitè’, a modified version of the French word, enables one to trace the possible presence of Victor Hugo in Pater’s earliest essay. In the opening chapter of Les Misérables, Hugo describes the pure nature of a deeply religious elderly lady. The woman here seems to be no longer a physical being, but has become, in her old age, a transparence, so to speak, as everything in her expresses her angelic nature. Hugo’s phrase ‘cette diaphanéité’ is very similar to Pater’s essay title. It is interesting that Hugo again uses the idiosyncratic word ‘diaphanéité’ when pondering the diaphanous creatures in his Les Travailleurs de la mer. Hugo attributes the quality of ‘diaphanéité’ to the ‘méduse’ (jellyfish) in the limpid sea water. Hugo’s Gilliatt thinks that ‘since living transparencies inhabit the water, other transparencies, equally living, might also inhabit the air.’ A Paterian echo from this passage could be found in Florian’s thinking of the ‘home-returning ghosts.’